Study causes of chronic energy deficiency of pregnant in the rural areas - Wiyono, Sugeng; Burhani, Annas; Harjatmo, Titus Priyo; Ngadiarti, Iskari; Prayitno, Nanang; ., Muntikah; Purbaningrum, Ratih Putrbanungtyas; ., Westa; Erowati, Dewi; Fahira, Farha (International Journal Of Community Medicine And Public Health, 2020)
Background: Chronic energy deficiency (CED) is one of the malnutrition problems that often occurs in pregnant, caused by lack of energy in a long period of time. One of the effects of pregnant suffering from CED is to increase the risk of maternal and short baby mortality. Method: The study was conducted in 8 villages of Kemranjen Subdistrict, Banyumas, Central Java, Indonesia in 2019. A cross sectional research design with population is that has pregnant. A sample of 130 pregnant was taken incidentally, with inclusion criteria that be able to do interviews and anthropometric measurements, while as the exclusion criterion was that pregnant were suffering from illness that could not be measured. Results: Most of the age was over 30 years and 9.2% suffered from CED. Nutrient intake is mostly less than 80.0% of the nutrition adequacy rate (RDA). The average intake of macro nutrients is 28.05%, the average micronutrient intake is 27.70%. Most graduated were from high school, worked as housewives, consumed supplements, additional food, and added blood tablets and drank milk, suffered from upper respiratory infections (ARI), high blood pressure, and diabetes mellitus, did not get complete immunizations. Conclusion: There were no significant differences in CED based on energy intake (p=1.00), protein intake (p=1.00), fat intake (p=0.179) and carbohydrate intake (p=0.460), work status (p=0.216) and education (p=0.553) and consuming additional food (p=0.225).